TANGGUNG JAWAB BADAN PENDAPATAN DAERAH DALAM IMPLEMENTASI PENINGKATAN PENDAPATAN DAERAH BERDASARKAN PERATURAN DAERAH KABUPATEN KAMPAR NOMOR 10 TAHUN 2011 TENTANG PAJAK SARANG BURUNG WALET DI KABUPATEN KAMPAR - Sarah Nanda Jelita; Firdaus Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
This study discusses the responsibility of the regional revenue agency in the implementation of increasing regional income based on the local regulation of the Kampar Regency number 10 of 2011 concerning the swallow's nest tax in the Kampar Regency. Article 2 paragraph (5) states that the taxpayer of swallow's nest tax is an individual or entity that makes efforts to collect and/or certify swallow's nests. And the basis for the imposition of a bird's nest tax is the selling value of a swallow's nest. However, what is in the field shows that the implementation of regional regulations is not going well.The type of legal research used by the author is a sociological legal research type. This research was conducted in Kampar Regency. Sociological legal research uses primary data and secondary data, while the population and sample are parties related to the problem studied, namely the Kampar Regency Regional Revenue Agency, the Kampar Regency House of Representatives and the owner of swallow's nest in Kampar Regency. Data collection techniques in this study with literature review, interviews and questionnaires.From the results of this study, the author concludes that the Kampar district regulation number 10 of 2011 has not been implemented properly, because the new local regulation was implemented in 2019 even though the Kampar district regulation which regulates the swallow's nest tax has long been ratified, the obstacle to implementing local regulations is the weakness supervision from the government, late in making regent regulations, not yet bringing in potential taxes, and lack of public awareness of paying taxes.Keywords: Government - local regulation - swallow's nest tax